2009
DOI: 10.1002/ange.200904565
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted Acid Catalyzed Enantioselective Semipinacol Rearrangement for the Synthesis of Chiral Spiroethers

Abstract: Keine halben Sachen: Die im Titel genannte Umlagerung von 2‐Oxoallylalkoholen 1 in Gegenwart einer katalytischen Menge der chiralen Phosphorsäure (R)‐2 a oder ihres Silbersalzes (R)‐2 b liefert die Spiroether 3 in enantiomerenreiner Form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(19 citation statements)
references
References 61 publications
0
16
0
3
Order By: Relevance
“…[70] The authors also designed this reaction on the premise that protonation of vinyl ether starting materials by a chiral phosphoric acid should result in the formation of chiral oxocarbenium•phosphate ion pair intermediates. By employing the silver salt of 14a as a precatalyst, mild conditions were identified that are optimal for most substrates.…”
Section: Chiral Anion-directed Catalysismentioning
confidence: 99%
“…[70] The authors also designed this reaction on the premise that protonation of vinyl ether starting materials by a chiral phosphoric acid should result in the formation of chiral oxocarbenium•phosphate ion pair intermediates. By employing the silver salt of 14a as a precatalyst, mild conditions were identified that are optimal for most substrates.…”
Section: Chiral Anion-directed Catalysismentioning
confidence: 99%
“…[61] Das erste Beispiel einer asymmetrischen Gegenanionen-vermittelten Lewis-Säurekatalyse wurde 2007 von Antilla et al vorgeschlagen. [61] Das erste Beispiel einer asymmetrischen Gegenanionen-vermittelten Lewis-Säurekatalyse wurde 2007 von Antilla et al vorgeschlagen.…”
Section: Anwendungen In Der Lewis-säurekatalyseunclassified
“…[11] Recently, our research group and that of others have reported some examples of asymmetric bromination/semipinacol rearrangement reactions that are catalyzed by cinchona-alkaloid derivatives. [12] In light of our previous results, combined with our long-standing interest in semipinacol-rearrangement reactions, [13,14] we hypothesized that the fluorination/semipinacol rearrangement reaction could also be catalyzed by cinchona-alkaloid derivatives in an asymmetric manner (Scheme 2). Herein, we present our preliminary results on this reaction.…”
mentioning
confidence: 98%